2005
DOI: 10.1038/modpathol.3800366
|View full text |Cite
|
Sign up to set email alerts
|

Invasion patterns in stage I endometrioid and mucinous ovarian carcinomas: a clinicopathologic analysis emphasizing favorable outcomes in carcinomas without destructive stromal invasion and the occasional malignant course of carcinomas with limited destructive stromal invasion

Abstract: Stage I, low-grade endometrioid and mucinous ovarian carcinomas have an excellent prognosis. Published data have suggested that destructive stromal invasion, a relatively uncommon finding in these tumors, is a poor prognostic factor. We investigated this by studying all FIGO stage I, grades 1 and 2 (of 3) endometrioid and mucinous ovarian carcinomas that were surgically staged at the Memorial Sloan-Kettering Cancer Center from 1980 to 2000. We undertook a careful review of all available slides using current di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 27 publications
3
38
2
1
Order By: Relevance
“…Thus, the category of low-grade endometrioid carcinoma in our study will be controversial (carcinoma versus borderline) for some pathologists. Like the relationships between endometrial hyperplasia and endometrioid adenocarcinoma of the uterine corpus, both low-grade endometrioid carcinoma and endometrioid borderline tumor are closely linked within the continuous spectrum of endometrioid tumor and share histologically and biologically overlapping features [25,26]. Low-grade endometrioid carcinoma and endometrioid borderline tumor also have a favorable prognosis, as does MMBT [25].…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the category of low-grade endometrioid carcinoma in our study will be controversial (carcinoma versus borderline) for some pathologists. Like the relationships between endometrial hyperplasia and endometrioid adenocarcinoma of the uterine corpus, both low-grade endometrioid carcinoma and endometrioid borderline tumor are closely linked within the continuous spectrum of endometrioid tumor and share histologically and biologically overlapping features [25,26]. Low-grade endometrioid carcinoma and endometrioid borderline tumor also have a favorable prognosis, as does MMBT [25].…”
Section: Discussionmentioning
confidence: 92%
“…The degree of nuclear atypia was evaluated in the worst area of each type of stromal invasion (expansile or infiltrative) and was classified into 3 grades on the basis of previous description (12,17). Nuclear grade 3 was characterized by variation in size (using nuclear width) >3 times, coarse chromatin granules, and prominent nucleoli.…”
Section: Primary Ovarian Mucinous Adenocarcinomamentioning
confidence: 99%
“…KHUNAMORNPONG ET AL the introduction of the expansile invasive pattern in 1996 were reviewed (2,3,8,9,(11)(12)(13)(14)(15)(19)(20)(21)(22). The studies were included if they were case series reported in the English language and contained sufficient data regarding the classification of invasive pattern (infiltrative or expansile type, including specified extent criteria), tumor stage, and clinical follow-up results.…”
mentioning
confidence: 99%
“…[92][93][94][95][96][97] The expansile/confluent/non-destructive pattern of invasion is characterised by architecturally complex glands, cysts or papillae lined by atypical epithelium with minimal to no intervening stroma. The destructive/infiltrative pattern is characterised by haphazardly arranged glands, tubules, nests and cords of malignant cells infiltrating stroma with an associated oedematous, inflammatory or desmoplastic response.…”
Section: Pattern Of Invasionmentioning
confidence: 99%
“…Although several studies have shown the expansile pattern to herald a better prognosis, a recent population-based registry study of mucinous ovarian carcinomas was not able to prognosticate based on the distinction between the two patterns of invasion. [92][93][94][95][96][97] It is recommended that the pattern of invasion in mucinous ovarian carcinomas be recorded.…”
Section: Pattern Of Invasionmentioning
confidence: 99%